The Relationship between Customer Loyalty Program and Customer Retention at Tesco - Muhammad Eizuan Mohd Azan,; Wan Nurul Karimah , (Research in Management of Technology and Business, 2022)
Customer loyalty programs are becoming more popular as a powerful relationship marketing technique for increasing customer loyalty. The purpose of this study is to identify the relationship between customer loyalty program and customer retention at Tesco. This study focused on respondents who have used or purchased items at Tesco. To achieve the objective of the study, quantitative approach had been used and a survey had been conducted among Tesco’s customer with a response rate of 41.16%. The data collected was analyzed using descriptive analysis and correlation analysis. The result shows that there is a significant relationship between customer loyalty program and customer retention at Tesco. Based on the findings, most customers are more confident with Tesco’s own brand products. Therefore, Tesco should advertise more of their own brand products and should offer promotions through every channel including online. In addition, Tesco Clubcard users should get more benefits when buying Tesco own brand products. This study recommends that a similar study be conducted on other major supermarkets and sectors such as the banking, transportation or insurance. This study also recommends expansion of the scope particularly regarding loyalty programs other than Clubcards, vouchers, and discounts.